Factors associated with acute clinically important postoperative nausea and vomiting in high-risk patients undergoing laparoscopic gastrointestinal surgery: a secondary analysis of the FDP-PONV trial - Huang, Yabin; Zheng, Jielin; Gong, Ruirui; Li, Yanwei; Han, Jiaxin; Zheng, Zhinan (Frontiers in Medicine, 2025)
BackgroundClinically important postoperative nausea and vomiting (CIPONV) is a highly distressing experience for patients after surgery. CIPONV can occur during the acute phase (0–24 h after surgery) or the delayed phase (25–120 h after surgery), with the acute phase being the primary concern. This study aimed to elucidate the key influencing factors associated with acute CIPONV. This study is based on data from the FDP-PONV trial, which exclusively enrolled patients with 3 or 4 Apfel risk factors. Thus, the findings are specific to this high-risk subgroup.MethodsPatients participating in the FDP-PONV trial were all included in this study. Acute CIPONV was defined as the occurrence of postoperative nausea and vomiting (PONV) with a simplified PONV impact scale score of 5 or higher during 0–24 h after surgery. The least absolute shrinkage and selection operator was employed to identify the most relevant variables, followed by stepwise regression to refine key factors. A logistic regression model was constructed. Its discrimination was assessed by the receiver operating characteristic curve area under the curve (ROCAUC), and goodness of fit was evaluated via the Hosmer-Lemeshow test and calibration plots.ResultsAmong the 1,154 patients, 162 (14.04%) experienced acute CIPONV. Triple prophylactic therapy for PONV, higher preoperative plasma fibrinogen level and higher preoperative monocyte count were negatively associated with acute CIPONV. Motion sickness and/or history of PONV, higher preoperative serum potassium level and the use of quinolones as antibiotic prophylaxis were positively associated with acute CIPONV. Based on these factors, a logistic regression model was constructed. The model showed good discrimination, with ROCAUC of 0.714 (95% confidence interval, 0.675–0.753), an accuracy of 0.621, and good fit (non-significant Hosmer-Lemeshow test, aligned calibration). A nomogram was created for clinical use.ConclusionSix factors were identified as key influencing factors for acute CIPONV in high-risk patients undergoing laparoscopic gastrointestinal surgery, which can help clinicians better prevent the occurrence of acute CIPONV in their patients.